COVID-19 Prognosis in Children With Asthma - Javad Ghaffari (Mazandaran University of Medical Sciences, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new coronavirus disease that is highly contagious and affects all age groups of children. The incubation period of Coronavirus disease (COVID-19) ranges from 2 to 14 days. Diagnosis of COVID-19 is made by conducting nasal and pharyngeal swabs and analyzing sputum, stool, and blood samples for COVID-19 nucleic acid using reverse-transcription polymerase chain reaction (RT-PCR). A nasal swab is more sensitive and specific than a pharyngeal swab. Lung CT imaging is a confirmation and complimentary method which is more sensitive than RT-PCR analysis. The mortality rate of COVID-19 infection is very low in children. Treatment of COVID-19 is supportive care and home isolation for 2 weeks (1). The disease has now spread to most countries. Clinical manifestations of COVID-19 vary from asymptomatic to a severe form in children (2).